An ounce of prevention, a pound of uncertainty : the cost-effectiveness of school-based drug prevention programs - Caulkins, Jonathan P. (Jonathan Paul), 1965- (Rand, 1999)
Focuses on school-based drug prevention programs that have proven effective in formal evaluations. Effectiveness at reducing cocaine consumption is inferred from effectiveness at reducing marijuana initiation, and spillover effects on those not participating in the program are accounted for. Given substantial uncertainties in all pertinent factors, the cost-effectiveness estimation framework is constructed to permit easy substitution of alternate values at reader preference or as more information becomes available. The authors conclude that prevention can reduce lifetime cocaine consumption by 2 to 11 percent. Although these effects are small, prevention programs are inexpensive, so that the associated cost-effectiveness values bracket those of a range of enforcement strategies. Treatment, however, appears more cost-effective than prevention. A nationwide drug prevention program would cost only a tiny fraction of what the United States now spends on drug control, but its effect on the cocaine-using population would be modest and slow to accumulate.